Changes in Flood Regime of the Upper Yangtze River - Zhang, Yu; Fang, Guohua; Tang, Zhengyang; Wen, Xin; Zhang, Hairong; Ding, Ziyu; Li, Xin; Bian, Xinsheng; Hu, Zengyun (Frontiers in Earth Science, 2021)
River flooding affects more people worldwide than other natural hazards. Thus, analysis of the changes in flood regime caused by global warming and increasing anthropogenic activities, will help us make adaptive plans for future flood management. The non-stationary flood behavior in upper Yangtze River was examined comprehensively in terms of trend, change point, and periodicity with co-usage of different methods. Results show that there are decreasing tendencies in the corresponding series of annual maximum flood peak flow and flood volume in four out of six control stations, except Pingshan and Wulong station in Jinsha River and Wu River, respectively, and the flood peak occurrence time appears earlier mostly. The uniformity of flood process increases in four main tributaries while decreases in mainstream of the Yangtze River (Yichang and Pingshan station).The rates of both rising limb and recession limb of all the typical flood process flowing through the six stations are analyzed. 77.8% of the rates of rising limb decreased while 61.1% of the rates of recession limb increased, which is almost consistent with the variation reflected by the uniformity. The change points of most evaluation indicators happened in 1970s-1990s. The first main periodicity of evaluation indicators in Yichang is about 45 years, while that of other stations is about 20 years. Invalidity of stationarity in the flood series can be attributed to the intensified construction on major water conservancy projects, changes of underlying surface and influences of climatic variables. The contributions of both climatic control and the Three Gorges Dam to the variation of the annual flood peak in Yichang station was further quantitatively evaluated, which has verified that the construction of the TGD has played a positive role in peak-flood clipping.